2014
DOI: 10.3390/ijms15011026
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hepatic Tissue Blood Flow Using Xenon Computed Tomography with Fibrosis Progression in Nonalcoholic Fatty Liver Disease: Comparison with Chronic Hepatitis C

Abstract: AimsThe present study evaluated the utility of xenon computed tomography (Xe-CT) as a noninvasive diagnostic procedure for the measurement of hepatic tissue blood flow (TBF) in patients with nonalcoholic fatty liver disease (NAFLD) or chronic hepatitis C (CH-C).MethodsXe-CT was performed in 93 patients with NAFLD and in 109 patients with CH-C. Subjects were classified into one of three groups, based on fibrosis stage: group 1, no bridging fibrosis; group 2, bridging fibrosis; and group 3, liver cirrhosis. Corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
(37 reference statements)
1
11
0
Order By: Relevance
“…Since perfusion fraction represents the fraction of diffusion linked to microcirculation (blood volume), the decrease of perfusion fraction indicates a decreased perfusion in livers with NAFLD. Portal vein tissue blood flow (PVTBF) obtained from Xe‐CT was found to be lower in advanced NASH than in early NASH, as well as lower in early NASH than in simple steatosis, while hepatic arterial tissue blood flow (HATBF) did not significantly increase . Previously, DCE‐MRI parameters have been frequently used as predictive biomarkers for angiogenic activity in tumors.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Since perfusion fraction represents the fraction of diffusion linked to microcirculation (blood volume), the decrease of perfusion fraction indicates a decreased perfusion in livers with NAFLD. Portal vein tissue blood flow (PVTBF) obtained from Xe‐CT was found to be lower in advanced NASH than in early NASH, as well as lower in early NASH than in simple steatosis, while hepatic arterial tissue blood flow (HATBF) did not significantly increase . Previously, DCE‐MRI parameters have been frequently used as predictive biomarkers for angiogenic activity in tumors.…”
Section: Discussionmentioning
confidence: 94%
“…It is reasonable that HABR might be present in NAFLD as well. Recent studies using Xe‐CT showed that NAFLD resulted in the reduction of whole liver tissue blood including total arterial tissue blood flow (THTBF), PVTBF, and HATBF, but PVTBF was affected more obviously . This might lead to a relatively increased ratio of HATPF to THTBF, which causes the increase of HPoI.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations